STUDI LITERATUR ANALISIS DALAM INVESTASI SAHAM DI INDONESIA - Elly Yuniar Nitawati; Juliani Pudjowati; Nurul Iman (CV. ADIBA AISHA AMIRA, 2025)
Investment is a strategy carried out by individuals and companies as a means of developing funds, including through capital market investment in stock trading. Stocks are a form of activity carried out by purchasing at a low price, then the stock owner determines the right time to sell at a high price, so that the capital owner will get a profit in a relatively short or fast time. Investment in stocks is very promising with large profits, but also has very high risks. Stock market investors must understand the strength of stock prices and be able to predict stock developments effectively to generate profits. Therefore, investors need to conduct proper analysis to optimise investment returns. This study aims to analyse the performance of stock investment strategies in the Indonesian capital market. The results indicate that stock investment strategies based on fundamental and technical analysis can enhance investment returns and reduce risks.